High Arabian Sea productivity conditions during MIS 13 – odd monsoon event or intensified overturning circulation at the end of the Mid-Pleistocene transition? - G.-J. Reichart; E. Tuenter; M. Ziegler; L. J. Lourens (Copernicus Publications, 2010)
Marine isotope stage (MIS) 13 (~500 000 years ago) has been recognized as atypical in many paleoclimate records and, in particular, it has been connected to an exceptionally strong summer monsoon throughout the Northern Hemisphere. Here, we present a multi-proxy study of a sediment core taken from the Murray Ridge at an intermediate water depth in the northern Arabian Sea that covers the last 750 000 years. Our results indicate that primary productivity conditions were anomalously high during MIS 13 in the Arabian Sea and led to extreme carbonate dissolution and glauconitization in the deep-sea sediments. These observations could be explained by increased wind driven upwelling of nutrient-rich deep waters and, hence, by the occurrence of an exceptionally strong summer monsoon event during MIS 13, as it was suggested in earlier studies. However, ice core records from Antarctica demonstrate that atmospheric methane concentrations, which are linked to the extent of tropical wetlands, were relatively low during this period. This constitutes a strong argument against an extremely enhanced global monsoon circulation during MIS 13 which, moreover, is in contrast with results of transient climate modelling experiments. As an alternative solution for the aberrant conditions in the Arabian Sea record, we propose that the high primary productivity was probably related to the onset of an intensive meridional overturning circulation in the Atlantic Ocean at the end of the Mid-Pleistocene transition. This may have led to an increased supply of nutrient-rich deep waters into the Indian Ocean euphotic zone, thereby triggering the observed productivity maximum.